Darbaspēka nodrošināšanas pakalpojumu darbinieka nosūtīšana un noma tiesiskais regulējums pirms un pēc Eiropas Parlamenta un Padomes 2008. gada 19. novembra direktīvas 2008/104/EK par pagaidu darba aģentūrām ieviešanas - Marcinkeviča, Sandra (Latvijas Universitāte, 2012)
Bakalaura darbs "Darbaspēka nodrošināšanas pakalpojumu darbinieka nosūtīšana un noma tiesiskais regulējums pirms un pēc Eiropas Parlamenta un Padomes 2008. gada 19. novembra direktīvas 2008/104/EK par pagaidu darba aģentūrām ieviešanas" ir veltīts tādu darbaspēka nodrošināšanas pakalpojumu kā darbinieku nosūtīšana un noma izpētei. Autore strādājot personāla atlases un darbaspēka nodrošināšanas jomā, pēdējo gadu laikā pastiprināti saskārās ar jautājumiem, kas skar tieši darbinieku nomas tiesisko regulējumu un no tā izrietošiem problēmjautājumiem, kas rodas no neprecīzu terminu lietošanas un izskaidrošanas. Tika veikts pētījums, lai uzzinātu, kas ir tie normatīvie akti, kas regulē darbaspēka nodrošināšanas pakalpojumus, kā arī kādi tiesību aktu pilnveidojumi būtu nepieciešami, lai trīspusējās attiecības starp darbaspēka nodrošināšanas pakalpojumu sniedzēju, saņēmēju un darbinieku tiktu atbilstoši regulētas.

Bachelor’s issue „Legal basis of the workforce securing services posting of employees and personal lease before and after the implementation of the Directive 2008/104/EC of the European Parliament and of the Council of 19 November 2008 on temporary agency work” was written with aim to point out what is the legal basis of services, mentioned before are the actual problems in legal acts, terminology and appropriate use of correct legislation. Due to rapid changes in labour and employment market in previous five years, there were several cases what stimulated Author to explore more precise all legal acts what are related to industry of the workforce securing services. As temporary agency work is well know all around the world and each year increasing number of employed persons, there are many forms of employment forms what also can be offered by temporary agencies. Exploring EU legal documents and literature regarding TAW (temporary agency work), Author discovered that there are many terms what are not used or translated correctly or not used at all in Latvian legal acts. Temporary agency work (TAW) is a unique, ‘triangular’ form of employment, which involves the supply of workers by intermediary firms for assignments in other organizations.. Temporary agency work in an enlarged European Union was an important and often rapidly growing sector in most EU countries. Implementing EU Directive 2008/104/EK on temporary agency work in Latvian Labour Law with the latest amendments at 16th of June 2011was the one of the steps what has been done to establish and control the industry what is growing each year. Author indicates several changes in Labour law and other legislation rules what could give support for agencies what provide services mentioned before and also could protect workers from unexpected changes or violations of their rights.
Legal basis of the workforce securing services posting of employees and personal lease before and after the implementation of the Directive 2008/104/EC of the European Parliament and of the Council of 19 November 2008 on temporary agency work
Keywords: Juridiskā zinātne